A PRAGMATIC STUDY OF CENTERS FOR DISEASE CONTROL AND PREVENTION CONTROL(CDC)INSTRUCTIONS OF COVID-19 - Prof. Dr. Qasim Obayes Al-azzawi, Noor Al-Huda Kadhim Hussein (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Despite the wide coverage and potential effectiveness of the public sensitization about Covid-19, studies on the social management of Covid-19 have not investigated context-constrained language use and its effects on the citizens in the announcements and instructions about the disease. Accordingly, the present studyis an attempt to explore the pragmatic aspects of the language used in the instructions of the Centers for Disease Control and Prevention Control (henceforth CDC) of Covid-19. The presents study tries to answer the following questions: (1) What are the pragmatic actsgenerated by the different utterances of CDC instructions of Covid-19? (2) What are the pragmatic functions or perlocutionary effectsof these acts in these instructions as a context-sensitive language? Thus, the study mainly aims at (1) Pinpointing the pragmatic acts generated by the different utterances of CDC instructions of Covid-19. (2) Demonstrating are the pragmatic functions or perlocutionary effects of these acts in these instructions as a context-sensitive language. It is hypothesized that: (1) Various pragmatic functions manifested in the instructions such as co-opting, projecting, encouraging, emboldening and advising. (2) CDC instructions of Covid-19 exhibit certain pragmatic acts such as co-opting, projecting, advising that are generated for certain intentions such as creating awareness about the virus, living a healthy live devoid of Covid-19 virus and maintaining healthy habit for adults.Then, in order to achieve the aims of the study and test its hypotheses the following procedures are adopted: (1) Presenting a theoretical background about the some pragmatic notions that are relevant to the present study along with some literature review about CDC and its role in Covid-19 battle. (2) Analyzing some extracts CDC instructions of the Covid-19 according to an elected model based on Mey (2001) model of pragmatic acts.After analyzing the data, the study has come up with some conclusions that validate the hypotheses set in the first place.